Optimal Protein Structure Alignment Using Maximum Cliques - Strickland, Dawn M.; Barnes, Earl; Sokol, Joel S. (Operations Research, 2005)
In biology, the protein structure alignment problem answers the question of how similar two proteins are. Proteins with strong physical similarities in their tertiary (folded) structure often have similar functions, so understanding physical similarity could be a key to developing protein-based medical treatments. One of the models for protein structure alignment is the maximum contact map overlap (CMO) model. The CMO model of protein structure alignment can be cast as a maximum clique problem on an appropriately defined graph. We exploit properties of these protein-based maximum clique problems to develop specialized preprocessing techniques and show how they can be used to more quickly solve contact map overlap instances to optimality.